Estimating the prevalence, factors, and conditions associated with Parkinson disease: a population-based study in Peru - Antonio Bernabe-Ortiz; Rodrigo M. Carrillo-Larco (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: This study aimed to estimate the population-based Parkinson disease prevalence, and to explore potentially associated factors and conditions. A population-based survey was conducted in Northern Peru. Symptoms compatible with Parkinson's were defined using a validated Spanish questionnaire (≥ 42 points suggest Parkinson's). Potential factors (e.g., age, sex, etc.) and clinical conditions (e.g., depressive symptoms, perceived stress, etc.) associated with Parkinson's were assessed. In total, 1,609 subjects were included, mean age of participants was 48.2 (SD: 10.6), and 810 (50.3%) were women. Parkinson's prevalence was 1.6% (95%CI: 1.0; 2.4). Those aged ≥ 55 years, and those who reported using wood as fuel for household cooking had a Parkinson's prevalence from 3.5 to 4 times greater than those who did not. The presence of depressive symptoms, anxiety symptoms, perceived stress, poor sleep quality, and cognitive impairment was more common among those with Parkinson's, and quality of life in these participants was lower than those without Parkinson's. In conclusion, 1.6% of the population shows symptoms compatible with Parkinson's. Age and use of wood for household cooking were factors associated with Parkinson's. Several mental health conditions and lower quality of life were more frequent among those with Parkinson's. Appropriate strategies are required to detect, prevent, and manage Parkinson's cases.